THE EFFECT OF SITTING POSITION ON DURATION OF 3RD STAGE AND BLEEDING VOLUME OF 3rd & 4th STAGES OF LABOR IN AKBARABADI HOSPITAL, TEHRAN, IRAN, 2000-2001. - Amini, L; Jahanfar, Sh; Rahimiha, F; Jamshidi, R; Kashanyan, M (Iran University of Medical Sciences, 2002)
Background: Mother's position during labor has been a major of concern for faster, easier and more tolerable birth. In fact, changing of the position during labor can be introduced as a solution for dystocia, prolonged labor and labor arrest. Furthermore, pregnancy outcomes including post partum bleeding is affected by upright delivery position. Objective: To investigate the effect of sitting position on the following variables: duration 3rd stage of labor bleeding volume of the 3rd and 4th stages of labor. Design: Controlled-Randomized clinical trial. Sample: One hundred women including 50 subjects in Sitting position group (Case group) and 50 subjects in Lithotomy position group (comparative group).selected by consecutive sampling method. Results: The duration of the 3rd stage of labor was significantly lowered in case versus comparative group (P= 0.015). The volume of blood loss during the 3rd stage of labor was significantly greater in the case group in comparison with the comparative (p= 0.004). However, the volume of blood loss during 4th stage of labor was not significantly different in 2 groups. Conclusion: Although, sitting position was found shorten the 3rd stage of labor in this study, it is suggested that mothers be given the chance to choose their own position of delivery.